Personal Finance Transformation in the Digital Era: The Impact of Financial Technology on People's Economic Behavior - Deri Apriadi; Dessy Adelin; Primadonna Ratna Mutumanikam; Laela Lanjarsih (PT. Hafasy Dwi Nawasena, 2025)
The development of financial technology (fintech) has revolutionized the way people access, manage and make decisions in personal finance. The digitization of financial services not only offers convenience and efficiency, but also triggers significant changes in people's economic behavior, especially among the younger generation and urban groups. This study aims to systematically analyze how financial technology affects individuals' economic behavior in terms of consumption, investment, and financial planning. The method used is a systematic literature review of relevant scientific articles published between 2018 and 2025. The results show that financial technology has a positive impact in improving digital financial literacy, encouraging saving and investing behavior, and facilitating financial decision-making. However, there are also negative impacts such as increased impulsive consumption due to digital credit features, as well as technology adoption inequality between urban and rural communities. The implications of this study emphasize the importance of strengthening inclusive financial literacy and consumer protection as prerequisites for creating a safe and sustainable digital financial ecosystem.